Question and Answers Forum

All Questions      Topic List

Logarithms Questions

Previous in All Question      Next in All Question      

Previous in Logarithms      Next in Logarithms      

Question Number 50080 by F_Nongue last updated on 13/Dec/18

a) if f(x)=log(x+2), solve the equation:  2^(f(x−2)) ×2^(f(2x+2)) =4^(logf(x))

a)iff(x)=log(x+2),solvetheequation:2f(x2)×2f(2x+2)=4logf(x)

Answered by tanmay.chaudhury50@gmail.com last updated on 13/Dec/18

f(x−2)=log(x−2+2)=logx  f(2x+2)=log(2x+2+2)=log(2x+4)  logf(x)=log{log(x+2)+2}  2^(logx) ×2^(log(2x+4)) =2^(2log{log(x+2)+2})   logx+log(2x+4)=2log{log(x+2)+2}  log{x(2x+4)}=log{log(x+2)+2}^2   2x^2 +4={log(x+2)+2}^2   2x^2 +4=4+4log(x+2)+{log(x+2)}^2   2x^2 =4log(x+2)+{log(x+2)}^2   k^2 +4k−2x^2 =0   k=log(x+2)  k^2 +4k+4=2x^2 +4  (k+2)^2 =2(x^2 +2)  k+2=(√(2(x^2 +2)))   log(x+2)+2=(√(2(x^2 +2)))

f(x2)=log(x2+2)=logxf(2x+2)=log(2x+2+2)=log(2x+4)logf(x)=log{log(x+2)+2}2logx×2log(2x+4)=22log{log(x+2)+2}logx+log(2x+4)=2log{log(x+2)+2}log{x(2x+4)}=log{log(x+2)+2}22x2+4={log(x+2)+2}22x2+4=4+4log(x+2)+{log(x+2)}22x2=4log(x+2)+{log(x+2)}2k2+4k2x2=0k=log(x+2)k2+4k+4=2x2+4(k+2)2=2(x2+2)k+2=2(x2+2)log(x+2)+2=2(x2+2)

Commented by tanmay.chaudhury50@gmail.com last updated on 13/Dec/18

Commented by Pk1167156@gmail.com last updated on 14/Dec/18

nice sir

Terms of Service

Privacy Policy

Contact: info@tinkutara.com